The Use of Question Cards Techniques to Improve Students’ Speaking Ability at Class VII of Muhammadiyah Junior High School of Mataram - Humairaa Humaira; Isnainib isnaini; Hidayati Hidayati; Rima Rahmaniah; Irwandi Irwandi (Linguistics and ELT Journal, 2021)
This study aims at determining the effectiveness of using "Question Cards" in improving students speaking ability at class VII of SMP Muhammadiyah Mataram. This study is part of a pre-experimental study known as a pre-test and post-test group design, in which the sample is given a pre-test before treatment and a post-test after treatment. There was no control group in this investigation; instead, only one experimental group was used. This study takes a quantitative approach to its findings. The participants in this study were seventh-graders from Muhammadiyah Mataram Junior High School, who were divided into only one class of 16 pupils. Purposive sampling is the approach used. The use of the "Question Cards" strategy in increasing the speaking skills of SMP Muhammadiyah seventh grade students can be concluded as "successful" in this study. This is demonstrated by the students' pre-test and post-test scores, namely, the t-test score is 5.313, the consultation on the t- table at 99 percent points to 2.60, and it can be concluded that the comparison of t-test and t-table is 2.60 5.313, or in other words, the student's test results exceed the minimum standard of achievement.